Protective effects of taurine against renal ischemia/reperfusion injury in rats by inhibition of gelatinases, MMP-2 and MMP-9, and p38 mitogen-activated protein kinase signaling. (3rd October 2017) - Cavdar, Z; Ural, C; Celik, A; Arslan, S; Terzioglu, G; Ozbal, S; Yildiz, S; Ergur, UB; Guneli, E; Camsari, T; Akdogan, G
Abstract: Dysregulated expression of matrix metalloproteinases (MMPs) is closely associated with the pathogenesis of renal ischemia/reperfusion injury (I/R). The production of excessive reactive oxygen species (ROS) causes tissue damage. Increased ROS production causes activation of p38 mitogen-activated protein kinase (MAPK) signaling, which participates in gene regulation of MMPs, especially MMP-2 and MMP-9 (gelatinases). Taurine (2-aminoethanesulfonic acid) in mammalian cells functions in bile acid conjugation, maintenance of calcium homeostasis, osmoregulation, membrane stabilization, and antioxidation, antiinflammatory, and antiapoptotic action. We investigated the effects of taurine and the possible role of p38 MAPK signaling on regulation of MMP-2 and MMP-9 in a renal I/R injury model in rats. Rats were divided into three groups: sham, I/R, and I/R + taurine treated. After a right nephrectomy, I/R was induced by clamping the left renal pedicle for 1 h followed by 6 h reperfusion. Taurine was administered 45 min prior to induction of ischemia. Renal function was assessed by serum creatinine and blood urea nitrogen (BUN) levels. Tubule injury and structural changes were evaluated by light microscopy. Malondialdehyde (MDA) levels were analyzed by high performance liquid chromatography (HPLC). Superoxide dismutase (SOD) activity levels were measured using a colorimetric kit. mRNA expression of MMP-2 and MMP-9 was determined by real-time polymerase chain reaction. MMP-2 and MMP-9 activities were measured using a fluorimetric kit. Phosphorylated p38 (p-p38) and total p38 MAPK protein expressions were evaluated by western blot. Taurine pretreatment significantly attenuated renal dysfunction and histologic damage, such as renal tubule dilation and loss of brush borders. The pretreatment also decreased the MDA level and attenuated the reduction of SOD activity in the kidney during I/R. Taurine pretreatment also decreased significantly both MMP-2 and MMP-9 mRNA expression and MMP-9 activity induced by I/R. In addition, the activity of p38 MAPK signaling was down-regulated significantly by taurine administration. Inhibition of MMP-2 and MMP-9 expression and MMP-9 activity caused by taurine may be associated with suppression of p38 MAPK activation during I/R induced renal injury in rats. Therefore, taurine administration may prove to be a strategy for attenuating renal I/R injury.